RESISTANCE TRAINING IMPROVES CARDIOVASCULAR HEMODYNAMICS IN OLDER ADULTS: INVOLVING AUTONOMIC BALANCE AND THE IMMUNE SYSTEM (CIPEEX, 2025)
The study evaluated the effects of resistance training on cardiovascular and immune health in older adults. Sixty-nine participants were randomly divided into a control group and a training group, which performed resistance exercises three times a week for 12 weeks. Pre- and post-training assessments included measurements of heart rate, blood pressure, and hemodynamic analysis by impedance cardiography. Inflammatory biomarkers and functional capacity were also analyzed. The results showed that resistance training significantly improved several cardiovascular parameters, such as increased stroke volume, cardiac output, and heart rate variability, in addition to reducing systemic vascular resistance. There were also improvements in respiratory muscle strength and functional capacity, with an increase in the number of repetitions in the sit-to-stand test and elimination of oxygen desaturation during the test. In addition, training promoted positive effects on the immune system, reducing levels of interleukin 6 and tumor necrosis factor alpha, and increasing interleukin 10 and Klotho. It is concluded that resistance training can be an effective intervention to improve cardiovascular hemodynamics, autonomic balance, and immune response in older adults, in addition to improving muscle strength and functional capacity, thus promoting healthier aging.
Keywords: Older Adults; Resistance Training; Cardiovascular Hemodynamics; Immune System